Retraction notice to "Ameliorating effect of hypothalamic brain-derived neurotrophic factor against impaired glucose metabolism after cerebral ischemic stress in Mice" [J. Pharmacol. Sci. 118 (2012) 109-116] - Shinichi Harada; Wakako Fujita-Hamabe; Shogo Tokuyama (Elsevier, 2020)
This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/our-business/policies/article-withdrawal).This article has been retracted at the request of the Authors. In Figure 1C some of the numbers of the original raw data were changed. Hence, the Figures were different from real Figures obtained from original raw data and the significant difference in Figure 1C was not obtained.